Les Volcans Eteints Du Maroc: Patrimoine Geologique Encore Peu Connu "Etude De Cas" - Eddif, Aâtika; Ouazzani, Hassan; Sadkaoui, Driss; Tajd, Amina; Aghbal, Ahmed; Hamid, Ahmed (European Scientific Journal, ESJ, 2017)
The present study aims to identify the degree of knowledge with regard to the Moroccan volcanic inheritance known as "geosites". More precisely, it has to do with those of the Middle Atlas with the school students and the future teachers of the Sciences of Life and Earth (SVT). It also involves their reflection on the likely means to make known and to share this geological inheritance with the target population and with the general public. This, however, is aimed at sensitizing its conservation for pedagogical, scientific, and ecotouristic awareness. In order to answer our study’s objectives, we administered an anonymous questionnaire to 232 school students in 2nd year of the secondary school of the provincial delegations of education of Meknes and Sale, and to 26 future teachers of the SVT of the regional center for education and training professions in Meknes, Morocco. The results of the research showed that these volcanoes are unknown among respondents with proportions of 80% among school students and 8% among future teachers.